206:oral But sometimes you end up giving in and giving them what they're not entitled to, because it's too difficult to say no.'– A qualitative study among physicians and nurses on clinical priority-setting in oncology. (28th April 2022) - Miljeteig, Ingrid; Solheim, Helge Alsaker
Abstract : Background: Even in a generously funded health care system as the Norwegian, there are limits for what can be provided. Our objectives are to explore in which situations physicians and nurses find it hard to refuse the patients' requests or demand for treatment and care that is not prioritized or they are not entitled to, what kind of strategies they use in order to change the patients´ mind and how they justify their actions. Methods: Focus group interviews with interdisciplinary teams at Department of Oncology and Medical Physics and Department of Thoracic Medicine at Haukeland University Hospital, Norway. Findings were analyzed using systematic text condensation. Results: All the 63 participants had experienced patients asking for treatment, hospitalization or care which were not prioritized or the participants found to be less important to provide. While the nurses negotiated on issues like single room, longer hospital stay, earlier appointments or paid transportation, physicians reporting more disagreement when it came to the level of treatment. The physicians found it most difficult to refuse patients' request for promising new treatment available in other countries, but not prioritized by the Norwegian government. Strategies used to help patients accept their decisions included referring to policy and principles, introduce someone with more authority, focus on side effects and appeal to solidarity. Many lacked good, ethical acceptable strategies. All providers had experiences of giving in, and their justifications were lack of time to argue with the patients, that it was uncomfortable and to keep a good relationship with the patient. Discussion: How bedside priorities are done, and what strategies nurses and physicians are using when negotiating in these situations should get more attention and the providers should be trained to handle these challenges. Clear guidelines, leadership and meeting arenas to discuss and reflect with colleagues are important.